Breeding Alnus species for resistance to Phytophthora disease in the Iberian Peninsula - Cordeiro, Daniela; Pizarro, Alberto; Vélez, M. Dolores; Guevara, M. Ángeles; de María, Nuria; Ramos, Paula; Cobo-Simón, Irene; Diez-Galán, Alba; Benavente, Alfredo; Ferreira, Verónica; Martín, M. Ángela; Rodríguez-González, Patricia M.; et al. (Frontiers in Plant Science, 2024)
Alders are widely distributed riparian trees in Europe, North Africa and Western Asia. Recently, a strong reduction of alder stands has been detected in Europe due to infection by Phytophthora species (Stramenopila kingdom). This infection causes a disease known as alder dieback, characterized by leaf yellowing, dieback of branches, increased fruit production, and bark necrosis in the collar and basal part of the stem. In the Iberian Peninsula, the drastic alder decline has been confirmed in the Spanish Ulla and Ebro basins, the Portuguese Mondego and Sado basins and the Northern and Western transboundary hydrographic basins of Miño and Sil, Limia, Douro and Tagus. The damaging effects of alder decline require management solutions that promote forest resilience while keeping genetic diversity. Breeding programs involve phenotypic selection of asymptomatic individuals in populations where severe damage is observed, confirmation of tree resistance via inoculation trials under controlled conditions, vegetative propagation of selected trees, further planting and assessment in areas with high disease pressure and different environmental conditions and conservation of germplasm of tolerant genotypes for reforestation. In this way, forest biotechnology provides essential tools for the conservation and sustainable management of forest genetic resources, including material characterization for tolerance, propagation for conservation purposes, and genetic resource traceability, as well as identification and characterization of Phytophthora species. The advancement of biotechnological techniques enables improved monitoring and management of natural resources by studying genetic variability and function through molecular biology methods. In addition, in vitro culture techniques make possible large-scale plant propagation and long-term conservation within breeding programs to preserve selected outstanding genotypes.